Creating gameful experience in the object-oriented programming classroom: A case study - Thongmak, Mathupayas (The Online journal of applied knowledge management, 2018)
Gamification has become popular in education. However, gamified classroom activity together with assessment activity are not yet much explored. In this study, the gamification was tested by assigning students enrolling in a programming concept class (object-oriented programming using Java) to play a simple card game and contest their programs involving the card game with others. The simple card games are chosen to decrease an instructor’s burden. The results of the focus group discussions show that gamified classroom activity could enhance students’ problem solving skills, engagement, attention to the course content, enjoyment and friendship, understanding, and creativity. The gamified assessment activity also lets students have more time to solve problems, clearly understanding the problems, increasing their confidence, decrease recitation, and reduce their stress. Intrinsic motivation is the main construct driving students to engage in gamification, supported by students’ extrinsic motivation.